ANALISIS PENDAPATAN DAN EFISIENSI USAHATANI KUBIS DI DESA BUKIT ASRI KECAMATAN KAPONTORI KABUPATEN BUTON - Suriadi, Suriadi; Jasiyah, Rabiyatul; Arniase, Ni Made (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2020)
This study aims to (1) determine the income earned by cabbage farmers in Bukit Asri Village, Kapontori Sub-district, Buton Regency (2) Know the efficiency of cabbage farming in Bukit Asri Village, Kapontori Sub-district, Buton Regency. This research was conducted from February 2020 to March 2020 in Bukit Asri Village, Kapontori Sub-district, Buton Regency. The sample in this study were all farmers who worked cabbage totaling 20 people, the determination of the sample was done by census method by taking the whole population from the sample as many as 20 people. The data analysis method used the analysis of production costs, revenue analysis, income analysis, and analysis of the efficiency of the RC farming ratio. The results of this study indicate that cabbage farmers income in Bukit Asri Village, Kapontori Sub-district, Buton Regency with average revenue of IDR 11.185.800,- and an average total cost of IDR 3.585.350,- per planting season, so the average income the farmer is IDR 7.600.450,- per planting season. The efficiency of cabbage farming that from the RC ratio results, get an RC ratio of 3,12 > 1. This shows that each cost incurred in the amount of IDR 1.000,- then gives income of Rp 3.120,- with a profit of 2,120,-. It can be concluded that cabbage farming is profitable and can be developed. Keywords: Farm Efficiency, Cabbage, and Income